Protective Effects of Alpha-Lipoic Acid against 5-Fluorouracil-Induced Gastrointestinal Mucositis in Rats - Deniz Ceylanlı; Ahmet Özer Şehirli; Sevgi Gençosman; Kerem Teralı; Hüseyin Şah; Nurhayat Gülmez; Serkan Sayıner (MDPI AG, 2022)
Alpha-lipoic acid (ALA) is extensively utilized in multivitamin formulas and anti-aging products. The purpose of this study was to investigate the potential protective benefits of ALA on 5-fluorouracil (5-FU)-induced gastrointestinal mucositis in Wistar albino rats. Tissues from the stomach, small intestine, and large intestine were excised, and blood sera were obtained to identify biochemical indices such as TNF-α, IL-1β, MDA, GPx, SOD, MMP-1, -2, -8, and TIMP-1. A histopathological study was also performed. The results revealed mucositis-elevated TNF-, IL-1, MDA, MMP-1, -2, -8, and TIMP-1 levels in both tissues and sera, and these values dropped dramatically following ALA treatment. Reduced SOD and GPx activities in mucositis groups were reversed in ALA-treated groups. The damage produced by mucositis in the stomach and small intestine regressed in the ALA-treated group, according to histopathological evaluation. Consequently, the implementation of ALA supplementation in 5-FU therapy may act as a protective intervention for cancer patients with gastrointestinal mucositis. In light of the findings, ALA, a food-derived antioxidant with pleiotropic properties, may be an effective treatment for 5-FU-induced gastrointestinal mucositus, and prevent oxidative stress, inflammation, and tissue damage in cancer patients receiving 5-FU therapy.